Archaeological lidar in Greece: a summary of recent work - Knodell, Alex R. (Journal of Greek Archaeology, 2025)
of whole cities or previously unknown regional systems of settlement in the Maya Lowlands, the Amazon, and the jungles of southeast Asia have made headlines and gripped the popular imagination, as in well-known examples from Caracol in Belize or Angkor Wat in Cambodia. Mediterranean applications have received less acclaim, but are no less significant for understanding past landscapes. High-resolution elevation models and the unique ability of lidar to ‘see’ beneath vegetation offer archaeologists the opportunity to detect and map subtle variations in the landscape and features that may otherwise go unnoticed, often over large areas. In what follows, I provide some introduction to lidar-based archaeological research, a summary of published and ongoing work in Greece, and some key considerations for how this work may fit into wider dialogues concerning archaeological remote sensing as we move forward. Many of these topics are relevant for survey archaeologists working elsewhere as well. I argue that lidar holds tremendous potential for archaeological research in Greece, especially at a regional scale. Several innovative projects are well underway, but collective research agendas remain nascent. Archaeologists now have a crucial opportunity to work toward certain shared goals and deploy a common set of standards for good practice, related to methodological transparency and the generation of accessible and comparable datasets, both in publication and in archival practices.